Failures in the rehabilitation treatment with removable partial dentures. (November 2013) - Benso, Bruna; Kovalik, Ana C.; Jorge, Janaina H.; Campanha, Nara H.
Abstract Background. Despite being functional and having aesthetic benefits, the acceptance of patients regarding the use of removable partial dentures (RPDs) has been low. In part, this is due to the deleterious effects that causes discomfort to the patient. Success depends not only on the care expended by the patient, including daily care and oral hygiene, but also on common goals set by their professional and clinical staff, aiming beyond aesthetics, to incorporate issues of functionality and the well-being of patients. Methods and results. For rehabilitation treatment with RPDs to reach the desired level of success without damaging the support structure, all the steps (diagnose, cavity preparation, adaptation of the metal structures, functional of distal extension and posterior follow-up) in the rehabilitative treatment should be carefully developed. A literature review was carried out, searching through MEDLINE (PubMed) articles published between 1965 and December 2012 including clinical trials and reviews about the use of RPDs. Conclusions. This study describes factors that lead to failures and complications in oral rehabilitation through the use of RPDs and suggests possible solutions.